Microstructure and Mechanical Properties of Aluminum Matrix Composites Reinforced With In-Situ TiB2 Particles - Wu, Weiguo; Zeng, Tiancheng; Hao, Wenfeng; Jiang, Shiping (Frontiers in Materials, 2022)
The present article investigates the microstructure and mechanical properties of A356 matrix composite reinforced with TiB2 particles synthesized by the salt metal reaction of as-cast and T6 state. Microscopic observations of the prepared composites reveal that in-situ grown TiB2 particles are characterized with regular shapes and nearly uniform distributed in the A356 matrix. The clear interface between A356 matrix and TiB2 particles were observed. The detailed analysis of mechanical properties of synthesized composites of as-cast and T6 state show that Young's modulus the synthesized composites and its ultimate tensile strength(UTs) of increase with the increasing weight percentage (wt.%) of in-situ TiB2 particles in A356 matrix. But Poisson's ratio of synthesized composites decrease with the increasing of TiB2 particles wt.%. Young's modulus of composites increase up to 10.8% and Poisson's ratio decrease up to 3.2% by the reinforcement of TiB2 particles 5wt.% while compared to A356 alloy. With the increasing of TiB2 particle wt.%, yield strength of the composites decrease at first (when particles wt.% is less than 1%) then increase, but elongation and percent reduction in area increase at first and then decrease. Furthermore, T6 heat treatment can refine grain and effectively improve the mechanical properties of composites.